Efektivitas Pelayanan Kesehatan Di Puskesmas - Elvi Juliansyah (Universitas Riau, 2012)
This study focuses on the issue ofworking hours and working time is relatively short in Sungai Durian health center, which is 25hours per week with a population of 16.901 people served. This study aims to determine theeffectiveness of health services at the Puskesmas Durian River and explain the factors that canimprove health care. This study uses qualitative research methods to approach the subject ofresearch using interview and documentary techniques. This study result show that: health serviceshave been effective at the Puskesmas Sungai Durian in accordance with the wishes and needs ofthe community, with good service quality, speed of service is highly dependent on the number ofpatients, it is easy to get service, the service provided free of charge, and factors that can improvehealth care, which is carried out continuously from 08:00 to 12:00 on weekdays, health servicesperformed by medical staff, and free health services with a relatively short time.